Foreign Workers And Migration In Malaysia: Legal Issues - Othman, Siti Awanis; Rahim, Rohani Abdul (Universiti Sains Malaysia, 2016)
Labour migration is a phenomenon that has been accepted by the local community and international levels. Movement of labour force from region to region and from country to country. International migration occurs when there is a movement by foreign workers that go across the borders of each country to another country. Many factors contribute to the phenomenon of migration between countries. The main attraction is a push factor. Economic situation of the country of origin and the lack of employment opportunities that has encouraged foreign workers to move out to other countries to get greater job opportunities. The rapid development of the country has led to the total labour force in great numbers. Indonesians, Bangladeshis, Philippines and workers from Southeast Asia and other southern countries migrate to Malaysia and worked in various economic sectors such as construction, manufacturing, agriculture, services and domestic. Positive results were of course the influx of foreign labour that has helped accelerate the pace of the national economy, especially in the industrial sector. Malaysia could not cope with the demand of labour needs. However, there were significant negative implications, especially in terms of social and labour repression. Given the large number of foreign workers, the crime rate was also found to have increased and often cause anxiety among local people. However, the government tried from time to time to reduce the number of foreign workers. This paper will discuss the issue on foreign workers' rights and migration in Malaysia and how the employer comply to them; the government efforts to manage the receiving and the returning of migrant labour via extensive policies, regulations and domestic laws and finally to investigate the latest planning by government in 11th Malaysia Plan in the effort to pursue the 2020 vision and to become a develop country in the near future.